There is a Crack in Everything-Education and Religion in a Secular Age - (Ina) ter Avest, K. H. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
There are two constants in academic and theological discourse throughout history, they are the debate around secularization and the dialogue concerning the intersection of religion and education. Each age has had its debate about modernizing forces that drive concerns of impending secularization. In this publication this theme is approached from perspectives of teachers, of students, of policy makers and situated in a politico-historical context. Aware of the fact that in today's plural societies one sacred canopy is non-existent anymore, cracks of the sacred canopy/canopies are described, as well as 'the light that gets in', the possible and challenging ways out are roughly sketched. We expect that each of the contributions of scholars of the East and the West, of the North and the South, and their presented examples and case studies, will stimulate the ongoing exploration and elaboration on the relationship between education and religion in todays' and the coming world - work-in-progress for coming generations.